An Isolated Iliac Wing Stress Fracture in a Male Marathon Runner: A Case Report. Issue 2 (April 2021) - Iizawa, Norishige; Sonoki, Kentaro; Obara, Yoshinori; Kataoka, Tatsunori; Majima, Tokifumi
Abstract : Case: A 49-year-old man, who had started jogging 3 months before his first participation in a marathon race, presented with acute pain and difficulty walking that began during the marathon race. Tumors and bone metabolism factors were ruled out by blood examination and various imaging findings. Isolated iliac wing fatigue fracture was diagnosed and treated with conservative therapy. Conclusion: This is the first English-literature report we know of an isolated iliac wing stress fracture in a male marathon runner without underlying disease. Our study highlights the importance of considering this rare fracture when diagnosing patients presenting with iliac pain.